The ignition characteristics of dual-fuel spray at different ambient methane concentrations under engine-like conditions. (25th January 2023) - Wei, Yi; Zhang, Zunhua; Li, Xucheng; Li, Gesheng; Zhou, Mengni; Belal, Belal Y.
Highlights: Kinetic interactions in dual-fuel spray ignition process are considered. Both the first- and second-stage ignition delay times are prolonged at higher ϕ CH4 . A detailed chemistry of the first-stage ignition process is analyzed. Time evolution of the dual-fuel spray ignition is visually illustrated. Heat release rate distributions of major exothermic reactions are presented. Abstract: In the present study, dual-fuel ignition process of pilot diesel spray injection into a natural gas-air mixture under engine-like conditions is numerically investigated via large-eddy simulation (LES). Methane and n -dodecane are considered as surrogates for natural gas and diesel fuels, respectively. This study aims to provide understandings of kinetic interactions for dual-fuel spray during the ignition process. The effects of ambient methane concentration on the ignition delay times (IDTs), product distributions, and heat release rates (HRRs) during dual-fuel ignition process are emphasized. The results show that methane prolongs the IDT of n -dodecane, especially for the first-stage IDT. Kinetic analyses reveal that the competition for OH between the dehydrogenation reactions of methane (CH4  + OH <=> CH3  + H2 O) and n -dodecane (RH + OH <=> R + H2 O) results in the increasing first-stage IDT of pilot spray. Moreover, it is found that the retarding effect positively correlates with the methane concentration. For product distributions, it is observed that the transition of CH2 O from fuel-lean to fuel-rich regions is inhibited in the first-stage ignition. In the second-stage ignition, the concentration of CO is decreased as the methane concentration increases and the area with high CO concentration is gradually shifted to the downstream of the spray. In addition, HRRs of low-temperature exothermic reactions appear at the radial periphery as well as the head of the spray front; HRRs of high-temperature exothermic reactions are gradually shifted from the head to the center of the spray with the increase of ambient methane concentration. The HRRs of low- and high-temperature reactions are decreased with increasing ambient methane concentration, and the major reactions for heat release at various ambient methane concentrations are different.